Research on the Reform of Computer Software Teaching in Higher Vocational Education under the Background of Big Data - Li, Chuanwei (Journal of Theory and Practice of Social Science, 2025)
With the rapid development of big data technology, the demand for computer software talents in society is increasing day by day, and higher requirements are also put forward for their professional abilities and comprehensive qualities. As an important way to cultivate applied technical talents, vocational computer software teaching faces new challenges and opportunities. In the context of big data, how to carry out teaching reform, improve teaching quality, and cultivate high-quality computer software talents that meet market demand has become an urgent problem to be solved in higher vocational education. This article aims to explore the reform direction and strategies of computer software teaching in higher vocational education under the background of big data, and provide useful references for promoting the development of computer software teaching in higher vocational education.